Provision in Muslim Families: Dogma, Role Shifts, and Realities in Bali and Banten - Makfiyati, Nida; Syafuri, B.; Ma'rifah, Nurul; Tarihoran, Naf'an (International Journal of Nusantara Islam, 2024)
This study aims to analyse the dogmas received by wives in Bali and Banten regarding their obligation to provide for their families. It also explores the shifting roles in the fulfilment of these obligations. Employing a qualitative research method with an empirical juridical approach, also known as a sociological approach, data were collected through observations, interviews, document analysis, and literature reviews. The data collected were analysed using Interpretative Phenomenological Analysis (IPA). The findings reveal differences in the dogmas received by wives in Bali and Banten. Women in Bali perceive the responsibility of earning a living as a shared duty between husbands and wives. In contrast, women in Banten view it as an absolute obligation of the husband; if the wife works, her role is merely to support the husband in meeting the family’s needs. The role shift in providing for the family occurs due to various factors, including economic needs, the wife’s skills being more relevant, the husband’s illness, prolonged absence without notice, death, and old age. Women in both Bali and Banten often assume the role of breadwinners for several reasons, such as the higher availability of job opportunities for women, economic challenges, higher educational attainment of wives, greater demand for women in the labor market, pre-marriage employment contracts, and inherited customs. This study offers insights into the interplay between traditional dogmas, economic realities, and shifting gender roles in Muslim families, contributing to discussions of gender dynamics and economic adaptation in Indonesia